Structural and Conductivity Studies of LiCo1–xMnxO2 Cathode Materials. Issue 1 (2nd January 2018) - Gangadhar, Vagmare; Shankaraiah, Chiliveri; Prasad, Guduru
Abstract : Present work aims at improving the characteristics of cathode material LiCo1–x Mnx O2 for Li-battery by increasing the concentration of manganese. The titled compound LiCo1–x Mnx O2 (x=0.0(LCO), 0.2(LCM2), 0.4(LCM4), 0.6(LCM6), 0.8(LCM8) and 1.0(LMO)) is prepared by solid state and sol-gel reaction methods. The structural studies of all the powders calcined at 850°C temperature for 20 h in the air are undertaken through powder X-ray diffraction. The diffraction patterns of these compounds are consistent with the reported patterns and exhibit predominant peak (0 0 3) orientation at 2θ = 19.08° and also other characteristic planes. The lattice parameters and the density are also reported. The surface morphological studies carried out using scanning electron microscope indicates average grain size of around 600 nm. FTIR studies show characteristic vibrations at 253, 304, 823, 1402 and 1619 cm –1 in the material. DC conductivity studies of the samples are measured from room temperature to 500°C and activation energies are calculated. These results are interpreted to understand the charge transport in the material. GRAPHICAL ABSTRACT: